Peranan Guru dalam Pengelolaan Pembelajaran Siswa Sekolah Minggu Buddha Vihara Ratna Vidya Loka Banyumas - Sarlina Gotami (Jurnal Ilmiah Kampus: Sati Sampajanna, 2023)
In the management of learning, the teacher plays a very important role. The teacher is the executor of the teaching and learning process so that the success of his teaching will determine the success of education in general. The results of the theoretical study show that learning management in the functional tasks of the teacher will be carried out effectively and efficiently if the teacher is able to carry out his role as manager of instruction in creating learning situations through the use of teaching and learning facilities. This research is a qualitative descriptive study. The data sources in this study were SMB teachers and SMB volunteers at Ratna Vidya Loka Vihara. The data collection technique uses source triangulation and the collected data is analyzed using the Miles and Huberman analysis technique. The role of the teacher in managing SMB learning at the Ratna Vidya Loka Temple has been carried out but is not optimal enough where the role of a teacher in learning management has tried to be a learning resource, manager, mentor, motivator and evaluator for students for the sake of the SMB being held at the Ratna Vidya Loka Vihara.